Outcomes of patients with renal monoclonal immunoglobulin deposition disease. Issue 11 (29th August 2016) - Kourelis, Taxiarchis V.; Nasr, Samih H.; Dispenzieri, Angela; Kumar, Shaji K.; Gertz, Morie A.; Fervenza, Fernando C.; Buadi, Francis K.; Lacy, Martha Q.; Erickson, Stephen B.; Cosio, Fernando G.; Kapoor, Prashant; Lust, John A.; et al.
Abstract : Recent reports suggest that deep hematologic responses to chemotherapy are associated with improved renal outcomes in monoclonal immunoglobulin deposition disease (MIDD). Here we describe the long term outcomes and identify prognostic factors after first line treatment of the largest reported series of patients with MIDD. Between March 1992 and December 2014, 88 patients with MIDD were seen at Mayo Clinic, MN. Renal responses were defined using criteria used for light chain amyloidosis (AL) or those used by the IMWG. Sixty‐one (69%) patients had a GFR < 30 mL/min/1.73 m 2 and 16 (18%) were on renal replacement therapy at diagnosis. The interval between albuminuria or elevation in creatinine and MIDD diagnosis was 12 months suggesting a delay in diagnosis. Thirty‐seven patients (42%) had at least a hematologic CR/VGPR. Fifty‐three (60%) received an autologous stem cell transplant (ASCT) or proteasome inhibitor (PI)‐based treatments. Patients receiving ASCT or PI‐based therapies were more likely to achieve at least a hematologic CR/VGPR compared to those receiving other therapies: 66% vs 2%, p < 0.0001. Patients that achieved a hematologic CR were more likely to achieve a renal response (53% vs 24%, p = 0.001). Five year overall and renal survival for the entire cohort was 67% and 57%, respectively. In multivariate analyses, a baseline GFR < 20 mL/min/1.73 m 2 and a renal response (using AL or IMWG criteria) were independently predictive of progression to dialysis. This study confirms that deep hematologic responses, best achieved with ASCT or PI‐based therapies, are a prerequisite to achieving renal responses. Am. J. Hematol. 91:1123–1128, 2016. © 2016 Wiley Periodicals, Inc.